The clinical spectrum of bulbar conjunctival rhinosporidiosis - Prasansha Narnoli; Suryasnata Rath; Samir Mohapatra; Mukesh Jain; Devjyoti Tripathy (Indian Journal of Ophthalmology)
Purpose: To report the clinical spectrum of bulbar conjunctival rhinosporidiosis at a tertiary eye care oculoplastics facility. Methods: Retrospective chart review of biopsy-proven ocular and adnexal rhinosporidiosis over a five-year period (2017–2022). Demographic details, clinical presentation, management interventions, and outcomes in a series of cases with bulbar conjunctival rhinosporidiosis were documented and analyzed. Results: A total of 14 cases of biopsy-proven bulbar conjunctival rhinosporidiosis were included in this study. These formed 22.2% of all cases of ocular adnexal rhinosporidiosis and 46.7% of all conjunctival cases diagnosed within the study period. All the cases underwent surgical excision of the conjunctival mass with five (35.7%) requiring a scleral patch graft for scleral thinning with or without staphyloma formation. Most patients had a good outcome on medium to long-term follow-up. Conclusions: Even though tarsal conjunctival involvement is reported as the most common form of conjunctival rhinosporidiosis in the literature, in our series, bulbar conjunctival disease comprised nearly half of all conjunctival cases, and over 20% of all adnexal cases. Most appear to do well with complete surgical excision of the granuloma. Rarely, long-standing cases may develop scleral thinning with or without staphyloma formation which may need major tectonic support to protect the integrity of the eyeball. Most of these also appear to do well on medium to long-term follow-up.